Hiperrealitas pada Media Sosial Pengguna Instagram di Kalangan Mahasiswa - Fadil Nurmansyah (STAI DDI Kota Makassar, 2021)
Currently Instagram social media is a need that is highly prioritized by students. Even students have made Instagram a social reality. The research entitled